PaCTS 1.0: A Crowdsourced Reporting Standard for Paleoclimate Data. Issue 10 (24th October 2019) - Khider, D.; Emile‐Geay, J.; McKay, N. P.; Gil, Y.; Garijo, D.; Ratnakar, V.; Alonso‐Garcia, M.; Bertrand, S.; Bothe, O.; Brewer, P.; Bunn, A.; Chevalier, M.; et al.
Abstract: The progress of science is tied to the standardization of measurements, instruments, and data. This is especially true in the Big Data age, where analyzing large data volumes critically hinges on the data being standardized. Accordingly, the lack of community‐sanctioned data standards in paleoclimatology has largely precluded the benefits of Big Data advances in the field. Building upon recent efforts to standardize the format and terminology of paleoclimate data, this article describes the Paleoclimate Community reporTing Standard (PaCTS), a crowdsourced reporting standard for such data. PaCTS captures which information should be included when reporting paleoclimate data, with the goal of maximizing the reuse value of paleoclimate data sets, particularly for synthesis work and comparison to climate model simulations. Initiated by the LinkedEarth project, the process to elicit a reporting standard involved an international workshop in 2016, various forms of digital community engagement over the next few years, and grassroots working groups. Participants in this process identified important properties across paleoclimate archives, in addition to the reporting of uncertainties and chronologies; they also identified archive‐specific properties and distinguished reporting standards for new versus legacy data sets. This work shows that at least 135 respondents overwhelmingly support a drastic increase in the amount of metadata accompanying paleoclimate data sets. Since such goals are at odds with present practices, we discuss a transparent path toward implementing or revising these recommendations in the near future, using both bottom‐up and top‐down approaches. Plain Language Summary: Standardizing the way data are described and shared is key to accelerating the progress of science. Building on recent advances in paleoceanography and paleoclimatology, we present the first community‐led reporting standard for such datasets. The Paleoclimate Community reporTing Standard (PaCTS) provides guidelines as to which information should be included when reporting data from various paleoclimate archives, as well as themes common to many fields, like uncertainty and other site‐specific information. The ultimate goal of this effort is to (1) make these datasets more re‐usable over the long term, and (2) provide a roadmap for implementing and revising the standard, as the field of paleoclimatology and its practitioners both evolve. The requirements are driven by the differing needs of data producers and the data consumers, who often have different goals in mind. Thus, agreeing on and writing up these requirements involves building consensus among the community to decide on their present and future goals. Key Points: First version of a crowdsourced reporting standard for paleoclimate data The standards arose through collective discussions, both in person and online, and via an innovative social platform The standard helps meet the interoperability and reuse criteria of FAIR (Findable, Accessible, Interoperable, and Reusable)